Hubungan Pemberian Asi Eksklusif Dengan Kejadian Stunting Pada Balita Di Puskesmas Weduar Kecamatan Kei Besar Selatan - Djurumana, Yohana; Tomasoa, Valensya Yeslin; Kainama, Mersy Delty; Leunupun, Trixie; Pelatta , Chendy Sofianty (Rena Cipta Mandiri, 2025)
One of the factors that causes stunting is the history of breastfeeding. Breast milk is the only ideal food that is the best and most perfect for babies to meet the physical and psychological needs of babies who are growing and developing. Exclusive breastfeeding is the provision of pure breast milk without any additional ingredients from the age of 0-6 months. The purpose of this study was to determine the relationship between exclusive breastfeeding and the incidence of stunting at the Weduar Health Center, South Kei Besar District. The research method used was quantitative using a cross-sectional study approach. The sample in this study was 30 toddlers using a total sample. The instruments used were questionnaires for breastfeeding and observation sheets for the nutritional status of toddlers. Bivariate analysis used the chi square test. The results showed that out of 30 toddlers who were not given exclusive breastfeeding, 11 toddlers were given exclusive breastfeeding and 19 toddlers were given exclusive breastfeeding. Bivariate analysis showed that there was a relationship between exclusive breastfeeding and the incidence of stunting (p value 0.0002). The conclusion of this study is that there is a relationship between exclusive breastfeeding and the incidence of stunting in toddlers at the Weduar Health Center, South Kei Besar District.